2015
DOI: 10.1177/0885328215590054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bio-based thermoplastic polyurethane elastomers containing isosorbide and polycarbonate diol and their biocompatible properties

Abstract: A new family of highly elastic polyurethanes (PUs) partially based on renewable isosorbide were prepared by reacting hexamethylene diisocyanate with a various ratios of Is and polycarbonate diol 2000 (PCD), via a one-step bulk condensation polymerization without catalyst. The influence of the isorsorbide/PCD ratio on the properties of the polyurethane was evaluated. The successful synthesis of the polyurethanes was confirmed by Fourier transform-infrared spectroscopy and 1 H nuclear magnetic resonance. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…FT-IR spectra of the three types of aligners before and after immersion in coffee were analysed, 38, 39, 40 and the IR peaks of the different groups are shown in Figure 4. FT-IR analysis confirmed that the Invisalign aligners were a PU-based material, 27, 28 the Angelalign aligners and/or retainers were a polycarbonate (PC)-based material, and the Smartee aligners were a PETG-based material.…”
Section: Resultsmentioning
confidence: 99%
“…FT-IR spectra of the three types of aligners before and after immersion in coffee were analysed, 38, 39, 40 and the IR peaks of the different groups are shown in Figure 4. FT-IR analysis confirmed that the Invisalign aligners were a PU-based material, 27, 28 the Angelalign aligners and/or retainers were a polycarbonate (PC)-based material, and the Smartee aligners were a PETG-based material.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of these soft segments in combination with various chain extenders has been investigated on degradation and physical/mechanical properties of the polyurethanes. Poly(ε‐caprolactone) (PCL) is one the most frequently used soft segment in biodegradable polyurethanes synthesis . However, degradation rate of PCL is rather slow because of its relatively hydrophobic nature and semicrystalline structure .…”
Section: Introductionmentioning
confidence: 99%
“…19 Polyester polyurethanes are known to be susceptible to hydrolytic degradation. 14,19 Poly(ε-caprolactone), 11,[20][21][22] poly(lactic acid), 12,23,24 poly(glycolic acid), poly(R-3-hydroxybutyric acid), 25 and their copolymers 14,[26][27][28][29] are extensively used as soft segments in SPUs. Effect of these soft segments in combination with various chain extenders has been investigated on degradation and physical/ mechanical properties of the polyurethanes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among different biopolymers, elastomers show high extensibility and recover to their original state when removing the stress. They are made of long polymer chains with excellent degree of flexibility and mobility …”
Section: Introductionmentioning
confidence: 99%